A MATLAB Toolbox for Findable, Accessible, Interoperable, and Reusable Atom Probe Data Science - Heller, Martina; Ott, Benedict; Dalbauer, Valentin; Felfer, Peter (Microscopy and Microanalysis, 2024)
Atom probe tomography (APT) data analytics have traditionally been based on manual analytics by researchers. As newer atom probes together with focused ion beam–based specimen preparation have opened APT to many more materials, yielding much more complex mass spectra, building up a systematic understanding of the pathway from raw data to final interpretation has increasingly become important. This demands a system in which the data and treatment can be traced, ideally by any interested party. Such an approach of findable, accessible, interoperable, and reusable (FAIR) data and analysis policies is becoming increasingly important, not just in APT. In this paper, we present a toolbox, written in MATLAB, which allows the user to store the raw and processed data in a standardized FAIR format (hierarchical data format 5) and process the data in a largely scriptable environment to minimize manual user input. This allows for the experiment data to be interchanged without owner explanations and the analysis to be reproduced. We have devised a metadata scheme that is extensible to other experiments in the materials science domain. With this toolbox, collective knowledge can be built up, and a large number of data sets can be analyzed in a fully automated fashion.
CRIS-Team Scopus Importer:2025-04-01
Keywords: atom probe data base; FAIR atom probe data science; HDF5; storage of APT data

An Atom Probe with Ultra-Low Hydrogen Background - Felfer, Peter; Ott, Benedict; Monajem, Mehrpad; Dalbauer, Valentin; Heller, Martina; Josten, Jan; Macaulay, Chandra (Microscopy and Microanalysis, 2021)
Atom probe tomography (APT) is a single-ion sensitive time-of-flight mass spectrometry method with near-atomic spatial resolution. In principle, it can be used to detect any chemical element, but so far hydrogen in the form of protium (H-1) had to be largely excluded. This is owing to the residual H emitted from the stainless-steel chambers and in-vacuum parts commonly used in atom probe instrumentation. This residual H is then picked up in the APT experiment. In this paper, we show that by replacing the stainless-steel chamber and in-vacuum parts with titanium parts, this residual H can largely be removed, thus enabling the direct imaging of H using APT. We show that besides the drastic reduction of H, also other contaminants such as O, OH, and H2O are reduced by employing this instrument. In the current set-up, the instrument is equipped with high-voltage pulsing limiting the application to conductive materials.
CRIS-Team WoS Importer:2021-12-31

A versatile cryo-transfer system, connecting cryogenic focused ion beam sample preparation to atom probe microscopy - Macauley, Chandra; Heller, Martina; Rausch, Alexander; Kümmel, Frank; Felfer, Peter (PLoS ONE, 2021)
Atom probe tomography (APT) is a powerful technique to obtain 3D chemical and structural information, however the ‘standard’ atom probe experimental workflow involves transfer of specimens at ambient conditions. The ability to transfer air- or thermally-sensitive samples between instruments while maintaining environmental control is critical to prevent chemical or morphological changes prior to analysis for a variety of interesting sample materials. In this article, we describe a versatile transfer system that enables cryogenic- or room-temperature transfer of specimens in vacuum or atmospheric conditions between sample preparation stations, a focused ion beam system (Zeiss Crossbeam 540) and a widely used commercial atom probe system (CAMECA LEAP 4000X HR). As an example for the use of this transfer system, we present atom probe data of gallium- (Ga)-free grain boundaries in an aluminum (Al) alloy specimen prepared with a Ga-based FIB.
CRIS-Team Scopus Importer:2021-02-12

Compensating Image Distortions in a Commercial Reflectron-Type Atom Probe - Heller, Martina; Ott, Benedict; Felfer, Peter (Microscopy and Microanalysis, 2024)
In atom probe tomography, the spatial resolution and accuracy of the data critically depend on the 3D reconstruction of the 2D detector data. Atom probes with a reflectron have an improved mass resolving power and must include a model of the imaging properties of the reflectron. However, for modern wide-angle reflectron instruments, these imaging properties are not trivial and need to be determined for the reflectron used. This is typically done by the instrument manufacturer, and due to the proprietary nature of the instrument design, the imaging properties are opaque to the user. In this paper, we provide a method to determine the imaging properties of a reflectron that can easily be carried out on commercial instrumentation. This method is used to provide the user with a transformation function from the provided detector data, which can already contain some corrections applied, to a virtual detector placed before the reflectron. From there on, 3D reconstructions can be carried out analogous to straight flight path instruments. Correction algorithms and reference data for Imago/CAMECA LEAP 3000, 4000, 5000, and 6000 series instruments are also provided.
CRIS-Team Scopus Importer:2025-04-01
Keywords: APT data correction; atom probe; reflectron

Dry reforming of methane over gallium-based supported catalytically active liquid metal solutions - Wolf, Moritz; de Oliveira, Ana; Taccardi, Nicola; Maisel, Sven; Heller, Martina; Khan Antara, Sharmin; Soegaard, Alexander; Felfer, Peter; Görling, Andreas; Haumann, Marco; Wasserscheid, Peter (Communications Chemistry, 2023)
Gallium-rich supported catalytically active liquid metal solutions (SCALMS) were recently introduced as a new way towards heterogeneous single atom catalysis. SCALMS were demonstrated to exhibit a certain resistance against coking during the dehydrogenation of alkanes using Ga-rich alloys of noble metals. Here, the conceptual catalytic application of SCALMS in dry reforming of methane (DRM) is tested with non-noble metal (Co, Cu, Fe, Ni) atoms in the gallium-rich liquid alloy. This study introduces SCALMS to high-temperature applications and an oxidative reaction environment. Most catalysts were shown to undergo severe oxidation during DRM, while Ga-Ni SCALMS retained a certain level of activity. This observation is explained by a kinetically controlled redox process, namely oxidation to gallium oxide species and re-reduction via H2 activation over Ni. Consequentially, this redox process can be shifted to the metallic side when using increasing concentrations of Ni in Ga, which strongly suppresses coke formation. Density-functional theory (DFT) based ab initio molecular dynamics (AIMD) simulations were performed to confirm the increased availability of Ni at the liquid alloy-gas interface. However, leaching of gallium via the formation of volatile oxidic species during the hypothesised redox cycles was identified indicating a critical instability of Ga-Ni SCALMS for prolonged test durations.
CRIS-Team Scopus Importer:2023-10-27

GaPt Supported Catalytically Active Liquid Metal Solution Catalysis for Propane Dehydrogenation-Support Influence and Coking Studies - Raman, Narayanan; Wolf, Moritz; Heller, Martina; Heene-Würl, Nina; Taccardi, Nicola; Haumann, Marco; Felfer, Peter; Wasserscheid, Peter (ACS Catalysis, 2021)
Supported catalytically active liquid metal solutions (SCALMS) of Pt in Ga (2 at.-% Pt) were studied in the temperature range of 500 to 600 °C for propane dehydrogenation. A facile synthesis procedure using ultrasonication was implemented and compared to a previously reported organo-chemical route for gallium deposition. The procedure was applied to synthesize GaPt-SCALMS catalyst on silica (SiO2), alumina (Al2O3), and silicon carbide (SiC) to investigate the effect of the support material on the catalytic performance. The SiC-based SCALMS catalyst showed the highest activity, while SiO2-based SCALMS showed the highest stability and lowest cracking tendency at higher temperatures. The selectivity toward propene for the SiO2-based catalyst remained above 93% at 600 °C. The catalysts were analyzed for coke content after use by temperature-programmed oxidation (TPO) and Raman spectroscopy. While the SiC- and SiO2-supported SCALMS systems showed hardly any coke formation, the Al2O3-supported systems suffered from pronounced coking. SEM-EDX analyses of the catalysts before and after reaction indicated that no perceivable morphological changes occur during reaction. The SCALMS catalysts under investigation are compared with supported Pt and supported GaPt solid-phase catalyst, and possible deactivation pathways are discussed.
CRIS-Team Scopus Importer:2021-11-19
Keywords: coking; dehydrogenation; gallium; platinum; SCALMS; supported liquid catalysis

High temperature oxidation resistance of physical vapor deposited Hf-Si-B-2 +/- z thin films - Glechner, T.; Bahr, A.; Hahn, R.; Wojcik, T.; Heller, Martina; Kirnbauer, A.; Ramm, J.; Kolozsvari, S.; Felfer, Peter; Riedl, H. (Corrosion Science, 2022)
Within physical vapor deposited Hf-Si-B-2 +/- z thin films, selective diffusion-driven oxidation of Si is identified to cause outstanding oxidation resistance at temperatures up to 1500 degrees C. After 60 h at 1200 degrees C, the initially 2.47 mu m thin Hf0.20Si0.23B0.57 thin film exhibits a dense oxide scale of only 1.56 mu m. The thermally induced decomposition of metastable Hf-Si-B-2 +/- z leads not only to the formation of Si precipitates within the remaining thin film (related to a non-homogenous Si distribution after the deposition) but also to pure Si layers on top and bottom of the Hf-Si-B-2 +/- z coatings next to the excellent adherend SiO2 based scales.
CRIS-Team WoS Importer:2022-07-15

High-temperature oxidation resistance of ternary and quaternary Cr-(Mo)-Si-B2-z coatings — Influence of Mo addition - Bahr, A.; Glechner, T.; Grimmer, A.; Wojcik, T.; Kutrowatz, P.; Podsednik, M.; Limbeck, A.; Heller, Martina; Ramm, J.; Hunold, O.; Kolozsvári, S.; Polcik, P.; et al. (Surface & Coatings Technology, 2023)
The Si-based alloying of transition metal diborides is a promising strategy to improve their limited oxidation resistance in high-temperature environments. In this study, we investigate the oxidation resistance of ternary and quaternary Cr-(Mo)-Si-B2-z coatings sputter-deposited from alloyed CrB2/TMSi2 targets (TM = Cr, Mo). The as-deposited Cr-(Mo)-Si-B2-z coatings are stabilized in the single-phased hexagonal AlB2-structure, except the high-Si containing Cr0.26Mo0.11Si0.24B0.39 presenting amorphous character. The Mo-containing Cr-Mo-Si-B2-z films exhibit relatively high hardness compared to their ternary Cr-Si-B2-z counterparts, obtaining up to 26 GPa due to the formation of (Cr,Mo)B2 solid solutions. The Si-alloying in ternary and quaternary coatings provides oxidation resistance up to 1200 °C, owing to the formation of highly protective double-layered scales consisting of SiO2 with a Cr2O3 layer on top, inhibiting oxygen inward diffusion. The quaternary Cr0.31Mo0.07Si0.15B0.47 coating is distinguished by superior oxidation resistance with lower porosity and void formation compared to the ternary Cr0.37Si0.16B0.47. Mo proved to be the key element for the higher stability and enhanced oxidation resistance due to the evolution of the MoSi2 phase at 600 °C. This phase formation controls the Si diffusion and mobility within the microstructure, thus reducing the porosity and governing the Si supply to form SiO2 scale. The quaternary Cr0.31Mo0.07Si0.15B0.47 coating maintained an oxidation resistance up to 30 h at 1200 °C by forming a 2.5 μm dense amorphous Si-based oxide scale with a thin Cr2O3 on top.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Chromium diboride; Disilicides; Oxidation resistance; Sputtering; Thin films

Miniaturized gas exposure devices for atom probe experiments - Ott, Benedict; Heller, Martina; Monajem, Mehrpad; Felfer, Peter (Microscopy research and technique, 2024)
To detect hydrogen in materials at the atomic scale, atom probe tomography is now regularly used. In order to avoid cumbersome cryo-preparation to suppress diffusion, often hydrogen is charged only into the finished specimen. Here, the use of hydrogen gas over electrochemical hydrogen has the advantage that the specimen is not contaminated with an electrolyte. So far, this “charging” has been done in large, expensive systems. Here, we introduce small devices that enable the exposure of atom probe specimens to hydrogen and potentially other gases, using only very small gas volumes. This enables the operation in regular laboratory environments without additional safety measures. These devices can be used to expose the specimen to hydrogen up to 10 bar/90°C. Higher temperatures may be attained with small changes. Validation of the success of charging with these setups is demonstrated through experiments employing deuterium charging of palladium atom probe tips. Research Highlights: Enabling the exposure of atom probe specimens to hydrogen and potentially other gases, using only very small gas volumes. Built setups can be assembled with little money and from freely available parts, making specimen charging much easier. Validation of the success of charging with these setups is demonstrated through experiments employing deuterium charging of palladium atom probe tips.
CRIS-Team Scopus Importer:2024-05-10
Keywords: atom probe; atom probe tomography; deuterium; deuterium gas charging

Pitting corrosion-Preferred chloride diffusion pathways in physical vapor deposited AlCrN coatings - Hudak, O. E.; Bahr, A.; Kutrowatz, P.; Wojcik, T.; Bohrn, F.; Solyom, L.; Schuster, R.; Shang, L.; Hunold, O.; Polcik, P.; Heller, Martina; Felfer, Peter; et al. (Corrosion Science, 2023)
Pitting corrosion of sputtered and arc evaportaed fcc-AlCrN coated low-alloy steel substrates was studied in a 0.1 M NaCl solution, using a three-electrode-cell. Depending on the deposition technique, several diffusion mechanisms were identified by high-resolution techniques (i.e. APT, TOF-SIMS). For arc evaporated AlCrN, incoherently embedded macro-particles provided the majority of fast-track diffusion pathways and pit-initiation sites, while their pristine coating matrix proved protective against chloride inward diffusion. Contrarily, the more coarse-grained sputtered AlCrN morphology with a highly orientated crystal growth featured diffusion paths along column boundaries, where chloride permeated the coating structure and initiated pit formations at the coating-substrate interface.
CRIS-Team WoS Importer:2023-01-13